Pengujian Beberapa Varietas Jamur Tiram Pada Kombinasi Mediaserbuk Ampas Tebu Dan Serbuk Gergajian Dengan Penambahan Molase Dan Limbah Ampas Tahu. - Ryan Fajar Sidik Siregar; Erwin Pane; Siti Mardiana (Universitas Medan Area, 2019)
Oyster mushroom is one of the most popular consumed mushrooms and also gives benefit for the body because it contains high nutrition and low fat. The goal of this research was to know and analyse the increase growth of some varieties of oyster mushroom on the bagasse media by adding molasses and tofu dregs. The research method was completely factorial randomized design (RAL Factorial) with two factors. The first factor was the media composition of sawdust and bagasse powder and The second factor was oyster musroom. The data analysis was tested by Anova and continued with duncan test if the results of variance were significantly different to very real. The results showed that the best treatment for mycelium growth on M1 media (100% bagasse + 1% molasses + 6% tofu dregs) with the best combination M2V3 (75% bagasse + 25% sawdust + 1% molasses + tofu dregs 6% on brown oyster mushroom). The largest stem diameter for V1 (white oyster mushroom) was 9.24 cm at the first harvest, and 9.01 cm the second harvest. The best length of the stalk in V3 variety (brown oyster mushroom) was 4.94 cm at the first harvest and 5.11 cm the second harvest. The best treatment on oyster mushroom production showed that variety V1 (white oyster mushroom) showed high production at the first harvest 130.25 grams and the second harvest 132.83 grams.